(untitled) (Annals of Medical Research, 2021)
Aim: Vertebral compression fractures lead to pain, significant spinal deformity and functional disability that severely limit the health-related quality of life. Although most patients respond to conservative treatment, it has been shown that more than 40% of patients do not achieve the desired reduction in pain within 1 year of onset of symptoms. Percutaneous balloon kyphoplasty is often used to relieve symptoms and accelerate the recovery of function. The aim of this study is to evaluate the pain and functional outcomes of patients treated with percutaneous balloon kyphoplasty. Material and Methods: Data of 113 patients who underwent percutaneous balloon kyphoplasty with the diagnosis of vertebra compression fracture between January 2015 and June 2019 were scanned. Preoperative and postoperative Numeric Rating Scale scores and Oswestry Disability Index (ODI) scores with complications were evaluated.Results: 113 patients with 154 vertebral fractures were treated. 86 were female and 27 were male. The mean age was 76.8 years. L1 (n=29) and Th12 (n=31) vertebral fractures were the most common. The mean duration of the procedure was 65.93 minutes, and the mean volume of cement was 5.02 ml. Cement leakage was observed at 12 cases. Permanent neuromotor deficits or mortality was not observed at any of the patients. Following percutaneous balloon kyphoplasty, the NRS and ODI scores significantly improved at the 6th month follow-up compared with preoperative scores, the NRS and ODI scores before the procedure were 8.8 and 49.2 whereas the postoperative NRS and ODI were 2.2 and 18.1, which is.Conclusion: Percutaneous balloon kyphoplasty is an effective procedure to control pain and improve health related quality of life. This method has the advantage of improving and restoring the vertebral height and kyphotic deformity in osteoporotic or pathological vertebral compression fractures.